2021
DOI: 10.1021/acsami.1c12240
|View full text |Cite
|
Sign up to set email alerts
|

Interphasial Engineering via Individual Moiety Functionalized Organosilane Single-Molecule for Extreme Quick Rechargeable SiO/NCM811 Lithium-Ion Batteries

Abstract: The individual moiety-functionalized organosilane single molecule, that is, 1,1,1,5,5,5-hexamethyl-3-[(trimethylsilyl)­oxy]-3-vinyltrisiloxane (TMSV), is investigated as an electrolyte additive for a less charge-consuming and viscoelastic solid electrolyte interphase (SEI) forming agent, finally accomplishing extremely quick (6 min) rechargeable SiO/NCM811 lithium-ion batteries. The moiety of the vinyl group serves with a poly­(ethylene oxide)-like viscoelastic SEI film on the SiO electrode, which provides a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…A SEI is known to be a complex mixture of compounds, and the physicochemical properties of the SEI are mostly determined by the type of solvents, electrolyte salts, and additives. Of these, the SEI properties including chemical composition, thickness, uniformity, and morphology can be controlled by various SEI-forming additives, and the related numerous studies have been reported. The most well-known and widely used SEI-forming additive for a graphite negative electrode is vinylene carbonate (VC). , By adding small amounts of VC into an electrolyte solution, the reinforcement of the SEI on graphite is achieved through formation of representative poly­(VC)-based polymeric compounds. , However, an overquantified or unoptimized SEI layer from the additive increases the impedance of LIBs, which leads to degradation of the battery performance, especially at high-rate or low-temperature conditions. Therefore, the advanced interface engineering by efficient control of additive decomposition without compromising other SEI functions is another important strategy to minimize the interphasial impedance, improving LIB performance.…”
Section: Introductionmentioning
confidence: 99%
“…A SEI is known to be a complex mixture of compounds, and the physicochemical properties of the SEI are mostly determined by the type of solvents, electrolyte salts, and additives. Of these, the SEI properties including chemical composition, thickness, uniformity, and morphology can be controlled by various SEI-forming additives, and the related numerous studies have been reported. The most well-known and widely used SEI-forming additive for a graphite negative electrode is vinylene carbonate (VC). , By adding small amounts of VC into an electrolyte solution, the reinforcement of the SEI on graphite is achieved through formation of representative poly­(VC)-based polymeric compounds. , However, an overquantified or unoptimized SEI layer from the additive increases the impedance of LIBs, which leads to degradation of the battery performance, especially at high-rate or low-temperature conditions. Therefore, the advanced interface engineering by efficient control of additive decomposition without compromising other SEI functions is another important strategy to minimize the interphasial impedance, improving LIB performance.…”
Section: Introductionmentioning
confidence: 99%
“…Varied strategies, such as materials modification, [18][19][20][21][22][23][24][25][26][27][28][29][30][31] electrolytes formulation, [32][33][34][35][36][37][38][39] and binders development, [40,41] have been taken to tackle the obstacles of SiO x -based anodes. As for materials modification, surface coating, [19][20][21][22][23][24] element doping [25][26][27] and prelithiation [28][29][30][31] strategies have been always adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Ni-rich cathode materials (LiNi x Co y Mn z O 2 , NCMs) are widely used as cathode active materials for LIBs because of their high specific capacity, and hence, NCMs are also the most promising cathode materials for sulfide-based all-solid-state batteries (ASSBs) because of their sophisticated characteristics. Meanwhile, the surface engineering of NCMs is highly important to fully utilize the characteristics of NCMs. , Owing to the high vapor pressure of Li at high calcination temperatures of NCMs, which leads to the formation of a Li-deficient phase, NCMs are synthesized using excess Li sources .…”
Section: Introductionmentioning
confidence: 99%